Pengaruh Pembelajaran Daring Dan Profesionalisme Guru Terhadap Kinerja Guru Di Masa Covid-19 - Ida Suryani (Universitas Negeri Makassar, 2022)
Covid-19 is an obstacle for all groups and is also a health crisis for humans in the world. In the world of education, Covid-19 has had a tremendous impact. This implies that the task of a teacher is so heavy in order to prepare students to achieve the educational goals that have been outlined. The method used in this research is descriptive quantitative using SPSS version 20.0. The role of the teacher is now very important considering the learning process can no longer meet face to face. Teachers must really make every effort so that students can understand the material presented online. From the results of the research and the results of data analysis that has been carried out, it can be concluded that there is an effect of online learning on teacher performance